The influence of advancing age on implantation of drug‐eluting stents. Issue 4 (25th November 2015) - Tian, Wenjie; Mahmoudi, Michael; Lhermusier, Thibault; Kiramijyan, Sarkis; Chen, Fang; Torguson, Rebecca; Suddath, William O.; Satler, Lowell F.; Pichard, Augusto D.; Waksman, Ron
Abstract : Background: The influence of age upon the use of drug‐eluting stents (DES) in patients aged ≥ 65 years is uncertain. The aim of this study is to investigate the impact of age increase in patients aged ≥ 65 years in the use of DES in patients undergoing percutaneous coronary intervention (PCI). Method: The study cohort comprised 8, 598 patients ≥ 65 years of age who underwent stent implantation from April 2003 to March 2014. We defined the first DES era as the period April 2003 to July 2008 and the second DES era as the period July 2008 to March 2014. Multivariable logistic regression was performed for both eras to assess the impact of age increase and analyze independent factors associated with DES implantation. Results: In the first DES era cohort, the two groups of patients differed in their risk factor profile with lower rates of male sex, diabetes, smokers, and hypercholesterolemia in those aged ≥ 75 years. There were more Caucasian and less African‐Americans in this age group. Furthermore, patients aged ≥ 75 years had lower left ventricular ejection fraction (LVEF) and baseline haematocrit concentration were more likely to present with an acute myocardial infarction (MI) than stable or unstable angina and had higher rates of a previous history for congestive heart failure (CHF), chronic renal insufficiency (CRI), and peripheral vascular disease (PVD). These differences were broadly similar for patients in the second DES era except for similarities in LVEF, presentation with unstable angina, and PVD, as well as a lower rate for previous PCI. DES use was reduced with increasing age in both the first (OR=0.78; 95% CI=0.69–0.89) and second DES era (OR=0.53; 95% CI=0.47–0.58). In both eras, DES use was less likely in current smokers, patients presenting with acute MI and cardiogenic shock, and those with a previous history of CHF. Conclusion: In patients aged ≥ 65 years, the use of DES decreased with increasing age. This observation was apparent in both the first and second DES era. © 2015 Wiley Periodicals, Inc.